20th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2015
DOI: 10.2514/6.2015-3610
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Investigation of a Thermal Compression Scramjet with OH Imaging

Abstract: Scramjet engines must be designed to operate over a range of Mach numbers. In order to maintain robust starting characteristics at low freestream Mach numbers, the inlet contraction ratio must be minimized, reducing performance at high Mach numbers. The technique of thermal compression can be used to maintain robust combustion at low mean pressure and temperature, improving the performance of low inlet contraction ratio engines over a range of Mach numbers. This paper examines a scramjet engine with a threedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Figure 28 shows part of the numerical simulation process. Vanyai et al [106] did an experiment on thermal compression scramjet based on OH imaging [107], and found that such three-dimensional air inlet of supersonic ramjet can generate pressure and temperature gradients of the fluid. The combustion of any part of the combustor was suppressed by injecting combustion fuel, hydrogen, or non-combusting helium to check how the combustion of these parts affected the pressure and temperature of the entire flow field, the concentration and production of OH radicals was depicted by OH chemiluminescence and planar laser induction fluorescence (PLIF) images see ( Figure 29) [108] so as to detect the chemical activity throughout the entire combustion process.…”
Section: Thermal Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 28 shows part of the numerical simulation process. Vanyai et al [106] did an experiment on thermal compression scramjet based on OH imaging [107], and found that such three-dimensional air inlet of supersonic ramjet can generate pressure and temperature gradients of the fluid. The combustion of any part of the combustor was suppressed by injecting combustion fuel, hydrogen, or non-combusting helium to check how the combustion of these parts affected the pressure and temperature of the entire flow field, the concentration and production of OH radicals was depicted by OH chemiluminescence and planar laser induction fluorescence (PLIF) images see ( Figure 29) [108] so as to detect the chemical activity throughout the entire combustion process.…”
Section: Thermal Control Systemsmentioning
confidence: 99%
“…Schematic diagrams of OH Chemiluminescence (left) and OH Planar Laser-Induced Fluorescence (right) of the combustion chamber of scramjets[106].…”
mentioning
confidence: 99%
“…The high-compression side ignites the fuel and promotes combustion, which increases the pressure and releases heat. This pressure increase compresses the low-compression side, promoting combustion there [23,122].…”
Section: Scramjetsmentioning
confidence: 99%
“…To evaluate the effect of increased injected mass flow rate, a case with φ = 0.13 was simulated with extra helium being injected with the fuel. Helium was chosen due to its similar molecular weight to hydrogen, and its previous use in experimental campaigns in impulse facilities at The University of Queensland as a replacement for fuel [122]. The total mass flow rate for fuel plus helium, and thus momentum ratio, was the same as that for fuel in the φ = 0.22 case.…”
Section: Effect Of Mass Flow Ratementioning
confidence: 99%
See 1 more Smart Citation